Varietal evaluation of double type tuberose (Agave amica) under Punjab conditions and their categorization using DUS Guidelines - SINGH, MANJINDER; BALA, MADHU; SHARMA , RISHU; DUBEY, R. K. (Journal of Ornamental Horticulture, 2024)
For commercial cultivation, it is imperative to characterize the available germplasm for selection and further improvement. The study was undertaken to observe morphological and reproductive traits of tuberose varieties and their categorization using DUS guidelines. The bulbs of five double type varieties were planted in a randomized block design and replicated thrice. Considerable differences among varieties were observed for various vegetative, floral traits and bulb yield parameters. Among the varieties evaluated, 'Arka Suvasini' exhibited maximum spike length (70.26 cm), number of florets per spike (56.86), diameter of florets (3.86 cm), weight of floret (2.62 g) and vase life (7.37 days). Also, as per DUS guidelines, all the varieties showed morphological variations with respect to leaf and floral characters and grouped in to respective categories.